Analysis of the Factors Influencing Public Decision to Use Conventional Banks from the Perspective of Islamic Banking - Marlina; Haslindah; Hartas Hasbi (Penerbit Jurnal Indonesia, 2025)
This study aims to conduct an in-depth analysis of the factors influencing the community’s decision to use conventional banks from the perspective of Islamic banking in Kawerang Village, Cina District, Bone Regency. The main issues addressed in this research are: what factors influence the decision of the people in Cina District, to continue using conventional banks instead of Islamic banks, and what obstacles they face in using conventional banks. This research is categorized as field research employing a qualitative approach, where field data is used to verify theories that emerge during the research process and are continuously refined as the study progresses. Data collection techniques include in-depth interviews, observation, and documentation. The research informants consist of residents of Kawerang Village who continue to use conventional banks rather than Islamic banks. Findings of this study reveal that the residents of Kawerang Village prefer conventional banks over Islamic banks primarily due to their greater familiarity with conventional banking institutions and the easier access to their services. As a result, conventional banks remain the preferred choice for banking transactions in the area